2016
DOI: 10.1016/j.celrep.2016.03.061
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Class of Neural Progenitors in the Drosophila Optic Lobe Generates Both Migrating Neurons and Glia

Abstract: SUMMARY How neuronal and glial fates are specified from neural precursor cells is an important question for developmental neurobiologists. We address this question in the Drosophila optic lobe, composed of the lamina, medulla, and lobula complex. We show that two gliogenic regions posterior to the prospective lamina also produce lamina wide-field (Lawf) neurons, which share common progenitors with lamina glia. These progenitors express neither canonical neuroblast nor lamina precursor cell markers. They bifurc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 78 publications
3
33
0
Order By: Relevance
“…The pOPC compartment can be further subdivided by the expression of the wingless and dpp signaling genes (Fig.1e) 30 . Cells in the wingless domain behave in a very distinct manner from the rest of the OPC, and have been described elsewhere 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…The pOPC compartment can be further subdivided by the expression of the wingless and dpp signaling genes (Fig.1e) 30 . Cells in the wingless domain behave in a very distinct manner from the rest of the OPC, and have been described elsewhere 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…Although the molecular mechanisms specific to type II lineage gliogenesis are poorly understood (Awasaki et al, 2008;Viktorin et al, 2011), gliogenesis has been widely studied in Drosophila and vertebrate nervous systems (Jones, 2005;Rowitch and Kriegstein, 2010). It has been shown that Notch signaling could either promote or repress gliogenesis, depending on the specific developmental context (Cattenoz and Giangrande, 2013;Chen et al, 2016;Gaiano and Fishell, 2002;Gho et al, 1999;Morrison et al, 2000;Udolph et al, 2001;Umesono et al, 2002;Van De Bor and Giangrande, 2001).…”
Section: Requirement Of Notch Signaling For the Gliogenic Switchmentioning
confidence: 99%
“…In vertebrate gliogenesis, Notch promotes the generation of Müller glia, astrocytes and Schwann cells, but represses oligodendrocyte differentiation (Kato et al, 2015;Morrison et al, 2000;Pierfelice et al, 2011). Similarly, Notch can either promote glial fate in specific lineages of the fly central nervous system (Chen et al, 2016;Udolph et al, 2001;Umesono et al, 2002) or inhibit gliogenesis in the sensory organ precursors of the Drosophila periphery nervous system (Gho et al, 1999;Van De Bor and Giangrande, 2001). In Drosophila, Notch regulates the expression of gcm, which is both necessary and sufficient to specify glial cells (Udolph et al, 2001;Umesono et al, 2002;Van De Bor and Giangrande, 2001).…”
Section: Notch Signaling Promotes Gliogenesis and Expansionmentioning
confidence: 99%
“…Lat (lamina-tangential) neurons, according to their structure and arborizations, seem to be involved in relaying feedback to the lamina from the circadian circuit (136). Finally, Lawf1 and Lawf2 (lamina wide-field) neurons provide broad field feedback from the medulla (23, 136). These seven neural types are derived from different sources than the LMCs and emerge from the medulla part of the OPC, the inner proliferation center (IPC), or neuroblasts in the central brain, making the lamina a composite of cells that arise from spatially independent precursors.…”
Section: Development: Generation Of Cell-type Diversitymentioning
confidence: 99%